Impact of feeding practices, socioeconomic, and demographic profiles of under five children with severe acute malnutrition - Gangaraj, Subba; Ghanshyam, Das (International Journal of Contemporary Pediatrics, 2017)
Background: The benefit of the early breastfeeding and timely imitation of complementary feeding as per locally availability of resource is well-documented. WHO recommend early initiation as soon as possible of the breastfeeding after birth as well as complementary feeding at 6 months of age. The objective was to know the feeding practices, socioeconomic and demographic profiles among the children with severe acute malnutrition (SAM). Methods: All under 5 children who fulfill the criteria of inclusion in the study. Various data were recorded and analyzed. Results: Only 22.36% and 31.57% of children received breastfeeding within 1 h and 1-4 h of birth, but exclusive breastfeeding till 6 months of age were found in 51.5% of children with SAM. About 42.1% of children had received complementary feeding between 6 months and 1 years of age and majority after 1 year of age, but no on were started on complementary feed before 6 months of age. Socio-economic, literacy, parity and demographic profiles had direct impacts that lead to malnutrition. Conclusions: The study has shown the existence of the under 5 children with SAM in nuclear and urban areas also.